Sustainable Development and Populism - Christian Kroll; Vera Zipperer (Ecological Economics, 2020)
All 193 UN member states have pledged to achieve 17 Sustainable Development Goals (SDGs), following the guiding principle to leave no one behind. At the same time, rising populist movements increasingly influence the political debate in many countries by challenging multilateral cooperation and liberal democracy. This paper contains the first empirical study of the relationship between the SDGs and populism. In order to analyse the nexus between these growingly important concepts, we introduce a new “Sustainability-Populism Framework”. It allows us to asses how the performance on the 17 SDGs over time relates to electoral support for populist parties, resulting in a classification of 39 countries into four categories. Moreover, in a regression analysis, we find that for each 1-point increase on the aggregate SDG Index (out of 100) over time, the vote share of populist parties on average drops by about 2 percentage points. Our results lend some support to the notion that a strong commitment to the SDGs (overall, as well as in particular to SDGs 1, 2, 11 and 15) could be part of an appropriate and effective answer to populism. We hope to initiate a timely debate on populism and sustainable development with our study, along with more research into this complex relationship.
Keywords: 330; Sustainable Development Goals; Agenda 2030; Populism